Preparation of W, N Codoped TiO2 with Enhanced Visible Light Response - Li, Xue; Liu, Yunyi (Asian Journal of Chemistry, 2012)
The W, N co-doped TiO2 nanoparticles have been synthesized by sol-gel method. The prepared photocatalysts were characterized by X-ray diffraction, field emission scanning electron microscopy, Fourier transform infrared spectroscopy and diffuse reflectance spectra. The results showed that the codoped photocatalyst with a spherical shape exhibited a smaller size than the undoped titania. Compared to un-doped TiO2, N-TiO2 and P-25, the absoption edge of the W, N co-doped TiO2 shifted to longer wavelength and its photocatalytic activity for degradation of methyl orange under Xe-lamp (350 W) was higher.